Originally posted by @joe-shmo
x = 1/(1/p + 1/q + 1/r + 1/s)
But I confess it took me quite a while before I got this one but it is easy once you see it as the solution simply comes from;
x = y / (a + b + c + d )
= 1 / ( (a + b + c + d ) / y )
= 1 / ( a/y + b/y + c/y + d/y )
= 1/(1/(y/a) + 1/(y/b) + 1/(y/c) + 1/(y/d))
= 1/(1/p + 1/q + 1/r + 1/s)
But I think there is something strange about this one that I just bet would make many people find it hard to get!
Just explaining the problem seems to me to somehow make it sound a lot harder to solve and more complicated than what it actually is.
This is one of the tiny bits of maths I will explain in my book.